Immunomodulation effects of collagen hydrogel encapsulating extracellular vesicles derived from calcium silicate stimulated-adipose mesenchymal stem cells for diabetic healing - Yen-Hong Lin; Yeh Chen; En-Wei Liu; Mei-Chih Chen; Min-Hua Yu; Cheng-Yu Chen; Chia-Che Ho; Tai-Yi Hsu-Jiang; Jian-Jr Lee; Der-Yang Cho; Ming-You Shie (Journal of Nanobiotechnology, 2025)
Abstract Diabetic wounds are characterized by chronic inflammation, reduced angiogenesis, and insufficient collagen deposition, leading to impaired healing. Extracellular vesicles (EVs) derived from adipose-derived mesenchymal stem cells (ADSC) offer a promising cell-free therapeutic strategy, yet their efficacy and immunomodulation can be enhanced through bioactivation. In this study, we developed calcium silicate (CS)-stimulated ADSC-derived EVs (CSEV) incorporated into collagen hydrogels to create a sustained-release system for promoting diabetic wound healing. CSEV exhibited enhanced protein content, surface marker expression, and bioactive cargo enriched with pro-angiogenic and anti-inflammatory factors. In vitro, CSEV-loaded collagen significantly reduced reactive oxygen species production, promoted cell proliferation and migration compared to standard EV-loaded collagen. Cytokine profiling revealed the upregulation of anti-inflammatory cytokines and extracellular matrix components, highlighting their immunomodulatory and regenerative potential. In vivo, histological evaluation of diabetic rabbit models treated with CSEV-loaded collagen revealed superior reepithelialization and organized collagen deposition, indicating accelerated wound closure. These findings underscore the potential of CSEV-loaded collagen hydrogels as an innovative and effective therapeutic platform for enhancing diabetic wound healing by simultaneously addressing inflammation and tissue regeneration. Graphical abstract